An outbreak of penicillin resistant Streptococcus pneumoniae investigated by a polymerase chain reaction based genotyping method. Issue 10 (October 1997) - Gillespie, S H; McHugh, T D; Hughes, J E; Dickens, A; Kyi, M S; Kelsey, M
Abstract : AIMS: To characterise the genotypes of penicillin resistant Streptococcus pneumoniae infecting patients in a care of the elderly ward and to study its transmission in a hospital environment. METHODS: Isolates of S pneumoniae were cultured from specimens obtained from patients who had been admitted to a care of the elderly ward where an outbreak had occurred. Penicillin resistant S pneumoniae were also obtained from a series of surveillance throat swabs taken from patients in the same ward. In addition, all penicillin resistant S pneumoniae isolated from specimens submitted for culture at the time of the outbreak were included. Four sensitive strains isolated from a routine microbiology laboratory were included as controls. A simple polymerase chain reaction (PCR) based genotyping method for the penicillin binding protein (PBP) genes 1a, 2x, and 2b was used to characterise the genotypes. RESULTS: Nine patients were infected with serotype 9 S pneumoniae. Four of these patients died; two deaths were directly attributable to the infection. Tested against a battery of haemolytic streptococci and other organisms found in the respiratory tract, only two false positive reactions for PBP 2x were found among S mitis. The method demonstrated that the outbreak strain had altered PBP 1a, 2b, and 2x genes, a pattern clearly distinguishable from other penicillin resistant strains isolated at the same time. CONCLUSIONS: This method is simple to perform and would enable many laboratories to characterise the genotype of penicillin resistant S pneumoniae and investigate transmission in their hospitals.